Cover Feature: Design, Synthesis, and Biochemical Evaluation of Alpha‐Amanitin Derivatives Containing Analogs of the trans‐Hydroxyproline Residue for Potential Use in Antibody‐Drug Conjugates (Chem. Eur. J. 40/2021). Issue 40 (22nd June 2021) - Matinkhoo, Kaveh; Wong, Antonio A. W. L.; Hambira, Chido M.; Kato, Brandon; Wei, Charlie; Müller, Christoph; Hechler, Torsten; Braun, Alexandra; Gallo, Francesca; Pahl, Andreas; Perrin, David M.
Abstract : Probing the hydroxyproline residue (Hyp) of alpha‐amanitin, this structural activity relationship study investigates the conformation and H‐bonding network of the first Hyp‐analogs of the extremely toxic, RNA polymerase II inhibiting, fungal octapeptide for its potential as a warhead in antibody‐drug conjugates. More information can be found in the Full Paper by A. Pahl, D. M. Perrin, et al. (DOI: 10.1002/chem.202101373 ).